The role of ILC2s in asthma combined with atopic dermatitis: bridging the gap from research to clinical practice - Luo, Yan-fang; Deng, Yu; Yang, Feng; Meiduosiji; Xiong, Xia; Yuan, Yu-lai; Ao, Su-hua (Frontiers in Immunology, 2025)
Asthma, a complex and heterogeneous respiratory disease, is often accompanied by various comorbidities, notably atopic dermatitis (AD). AD characterized by recurrent eczematous lesions and severe itching, can trigger or exacerbate asthma. Individuals with AD are 2.16 times more likely to develop asthma compared to the reference population. Furthermore, asthmatics with AD experience more severe and frequent emergency department visits and hospital admissions compared to patients with asthma alone. The close connection between asthma and AD indicates there are overlap pathophysiologic mechanisms. It is well-known that dysregulated type 2 (T2) immune inflammation is pivotal in the development of both AD and asthma, traditionally attributed to CD4+ type 2 helper T (Th2) cells. Over the past decade, group 2 innate lymphoid cells (ILC2s), as potent innate immune cells, have been demonstrated to be the key drivers of T2 inflammation, playing a crucial role in the pathogenesis of both asthma and AD. ILC2s not only trigger T2 immune-inflammation but also coordinate the recruitment and activation of innate and adaptive immune cells, thereby intensifying the inflammatory response. They are rapidly activated by epithelium alarmins producing copious amounts of T2 cytokines such as interleukin (IL) -5 and IL-13 that mediate the airway inflammation, hyperresponsiveness, and cutaneous inflammation in asthma and AD, respectively. The promising efficiency of targeted ILC2s in asthma and AD has further proven their essential roles in the pathogenesis of both conditions. However, to the best of our knowledge, there is currently no review article specifically exploring the role of ILC2s in asthma combined with AD and their potential as future therapeutic targets. Hence, we hypothesize that ILC2s may play a role in the pathogenesis of asthma combined with AD, and targeting ILC2s could be a promising therapeutic approach for this complex condition in the future. In this review, we discuss recent insights in ILC2s biology, focus on the current knowledge of ILC2s in asthma, AD, particularly in asthma combined with AD, and suggest how this knowledge might be used for improved treatments of asthma combined with AD.